Mitologi Sedekah: Penerapan Semiotika Roland Barthes pada Q.S. Al-Baqarah [2]: 271 - Habibie, Ilham Akbar; Hairul, Moh. Azwar (UIN Sultan Syarif Kasim Riau, 2023)
This research discusses the meaning of charity in interpreting Surah Al-Baqarah [2]: 271 using Roland Barthes' semiotic approach. The article focuses on revealing both denotative and connotative meanings, as well as discussing the signs found in Surah Al-Baqarah [2]: 271. The method employed in this research is qualitative, utilizing primary and secondary source analysis. Primary sources include classical and contemporary interpretations and Roland Barthes' book titled